ZIKRULLAH AS AN EMOTIONAL COUNSELING ON AMYGDALA FROM SCIENCE APPROACH - Jasafat Jasafat; Iskandar Ibrahim; Kusmawati Hatta (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
AbstractZikrullah is the main Islamic teaching that is able to soothe the heart has not been used in emotional counseling. Zikrullah as vibration affects the brain. M. J. Griffin conducted an analysis of the vibration relationship with humans. The relationship between sound and emotion is still being studied in the EEG room. The purpose of this paper is to discuss the relationship between zikrullah and emotional counseling from a scientific approach. The qualitative study data was sourced from 3 zikrullah leaders in Medan and 3 Aceh Utara. Support data refer to the work of Acehnese Ulama Shaykh Muhammad Muda Waly. This study will contribute to four aspects. First, the development of Islamic mysticism. Second, increasing public recognition of zikrullah as an emotional therapy for the brain. Third, to explain zikrullah as a legacy of Sufism scholars. Fourth, to resolve the incomplete mental problems in Aceh. The government can adopt the results of this study into public policy as social capital to strengthen the application of Islamic values in Aceh. The government can recommend a zikrullah counseling approach to mental hospitals, prisons, nursing homes, trauma rehabilitation centers and drug rehabilitation centers.Keywords: zikrullah, counseling, amygdala, neuroscience